EXPLORATIVE STUDY OF THE IMPACT OF DISTANCE LEARNING IN THE COVID-19 PANDEMIC ON ELEMENTARY SCHOOL - Prikustini, Vadlina Putry; Safitri, Nabilah Dwi; Magdalena, Ina (PROGRES PENDIDIKAN, 2021)
Since the COVID-19 outbreak, which requires all Indonesian citizens and even around the world to apply WFH (Work from Home) including all school residents in Indonesia who apply online or online-based learning at SDIT AR-RISAALAH. The implementation of online learning has consequences for a teacher to increase his role and competence because competent teachers will be better able to manage classes and carry out evaluations for students both individually and in class. This study aims to determine the impact of online learning experienced by teachers and students during the COVID-19 pandemic. This research uses case study research, wherein collecting data information with interview techniques, namely to find data on relevant matters. The results showed that the learning process during the pandemic changed by using a remote network. This has an impact on teachers because they are less than optimal in providing learning materials and disrupting the learning process which causes the expected learning objectives to not be achieved. So that it makes the material incomplete and the use of learning media in online learning is not optimal. Student assessment is also constrained by mere cognitive assessment. This research uses the case study method as the research method, by conducting interviews with 3 teachers and 3 students of SDIT AR-RISAALAH. Interviews were conducted in-person/offline by approaching the informants.